Spectroscopic and molecular modeling studies of binding interaction between bovine serum albumin and roflumilast - Wani TA (Drug Design, Development and Therapy, 2018)
Tanveer A Wani,1 Ahmed H Bakheit,1,2 Mohammed Nazam Ansari,3 Abdul-Rahman A Al-Majed,1 Bakr M Al-Qahtani,1,4 Seema Zargar5 1Department of Pharmaceutical Chemistry, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 2Department of Chemistry, Faculty of Science and Technology, Al-Neelain University, Khartoum, Sudan; 3Department of Pharmacology, College of Pharmacy, Prince Sattam Bin Abdulaziz University, Al Kharj, Saudi Arabia; 4Drug Sector, Saudi Food and Drug Authority, Dammam, Saudi Arabia; 5Department of Biochemistry, College of Science, King Saud University, Riyadh, Saudi Arabia Background: The binding interaction between bovine serum albumin (BSA) and roflumilast (ROF) was explored in this study. The binding of drugs to albumin plays a vital role in their pharmacokinetics and pharmacodynamics in vivo. The mechanisms involved in the interaction between BSA and ROF was studied using multi-spectroscopic experimental and computational approaches. Materials and methods: Spectrofluorometric experiments were used to determine the method of quenching involved and the conformational changes in the BSA. UV–visible spectroscopy synchronous and three-dimensional fluorescence spectroscopy were used to further explore the binding interaction mechanism. Results: The results suggested that the intrinsic fluorescence of BSA was quenched due to the formation of a static complex between ROF and BSA. Conformational changes in BSA were determined based on its interaction with ROF. The thermodynamic results suggested that the interaction between ROF and BSA was spontaneous and a hydrophobic interaction occurred between them. Site I of BSA was suggested as the site of interaction between ROF and BSA based on the site marker experiments. Conclusion: The molecular simulation results and the experimental outcomes were complimentary to each other and helped to identify the binding site and nature of bonds involved in the interaction between ROF and BSA. Keywords: roflumilast, bovine serum albumin, COPD, fluorescence, quenching